On Ancient Cults from the South of the Province of Dalmatia (А few examples from east Herzegovina) - Samardžić, Gligor (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Statues that testify about the religiousness of the Roman citizens exist in east Herzegovina (south of the province of Dalmatia) as well as in all areas within the Roman Empire. The spiritual life of the citizens from the south of the province of Dalmatia (east Herzegovina) reflected in the respect for a significant number of cults. The religion of an ancient man from east Herzegovina is represented, above all, by modest archeological findings and epigraph statues. It manifested itself in the respect for a significant number of cults that relied on Illyrian tradition, Roman and oriental deities.
Keywords: ancient cults; epigraph statues; the Roman Empire; the province of Dalmatia; east Herzegovina